India : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report, 2009)
India's financial system compares favorably internationally, but rising credit risk and liquidity pressures are putting it under strain. The staff report for India's 2008 Article IV Consultation discusses economic developments and policies. The authorities have already taken numerous welcome measures in response to the crisis. The Reserve Bank of India has been quick in reversing its policy stance and the reductions in interest rates, the cash reserve ratio, and the statutory liquidity requirement together with stepped-up open market operations have been fully warranted.